DETERMINANTS OF HOUSING INSECURITY IN A LOW INCOMESOUTH AFRICAN TOWNSHIP - N.P Mncayi (International Journal of Economics and Finance Studies, 2017)
The campaign to end povertyby 2030,as advocated by the World Bank,has multifacetedcomponents. Food security and abject poverty have received more attention;however,little attention has been focused on housing insecurity. This is important,especially giventhe fact that it iswidely acknowledged that housing satiates an essential human need forphysical security, dignity and prosperity,among other things. Housing, for some time,has been observed as crucial to individual and family functioning. As indicated byorganisations such as the United Nations Habitat, the importance of appropriate housingis explained by the fact that safe housing is seen as a basic need among other needs suchas food, all of which are regarded as central components of the security of ordinaryhouseholds, particularly in developing countries. In 2015, more than 1.5 billionpeopleinthe world were living in housing that was unsafe and inadequate, while in the meantime,millions experienced eviction from their homes every year, with at least 100 millionpeople becoming homeless on any given day.Therefore, it ispertinent to understand whatdetermines housing insecurity. The studyaims toinvestigatefactors thatdetermineshousing insecurity. Using data collected from Sharpeville and Bophelong, two lowincome townships in South Africa that are particularlyvulnerable to housing insecurity,the study employs amultinomiallogisticregression to investigate the effects of head ofhousehold and the general household characteristics on housing insecurity. Theresults ofthe regression analysis show that income, gender, number of people in the household andthe amount paid to bond or rent are significant predictors of housing insecurity.Contentious issues like access to land and job opportunities are areas of further study inunderstanding the multifaceted phenomenon of housing insecurity.